Diffusion Tensor Imaging Analysis Along the Perivascular Space Index in Primary Parkinson's Disease Patients With and Without Freezing of Gait. (1st December 2022) - Ruan, Xiuhang; Huang, Xiaofei; Li, Yuting; Li, E; Li, Mengyan; Wei, Xinhua
Highlights: DTI along the perivascular space (DTI-ALPS) is a sensitive approach for assessing the activity of the glymphatic system. Decreased DTI-ALPS index in PD patients with or without freezing of gait suggests glymphatic system dysfunction. Glymphatic dysfunction in PD individuals were highly related to motor symptoms and treatment complications. Abstract: Parkinson's disease (PD) is a common neurodegeneration disease associated with the abnormal deposition and spread of misfolded proteins (α-synuclein and Tau protein), which progressively damages the glymphatic system. This research intended to investigate the activity of the glymphatic system in PD individuals with freezing of gait (PD-FOG) and PD patients without it (PD-nFOG), as well as their relationship to the clinical neural scale. Diffusion tensor imaging (DTI) was performed in 28 PD-FOG individuals, 31 PD-nFOG individuals, and 34 healthy controls (HC). The DTI analysis along the perivascular space (DTI-ALPS) index was computed after post-processing of DTI images, representing brain glymphatic functions. The DTI-ALPS index was assessed for the association with the clinical variables. Compared to the HC group, the DTI-ALPS index of both PD-FOG and PD-nFOG patients was significantly decreased; however, no notable difference was found between the PD-FOG and PD-nFOG group. In addition, the DTI-ALPS index of PD-nFOG patients were positively correlated with disease duration, Unified Parkinson's Disease Rating-III Right (UPDRS-III R), UPDRS-III TOTAL, UPDRS-IV. Taken together, these findings highlighted the weakening of function of the glymphatic system in PD individuals, which is associated with motor symptoms and treatment complications. We speculate that treatment aimed at enhancing the flow and clearance of the glymphatic system may alleviate clinical symptoms of PD.